Thermal efficiency of different coverage materials in reduced models of animal husbandry facilities: A case study - De Castro A.C. (2017)
This study aimed to assess different combinations of coverage materials in reduced models of animal husbandry facilities based on thermal comfort indices. It was conducted in an experimental area of the Research Center in Ambience located in São Paulo State, Brazil (22°42'30" S and 47°38'00" W). The performance of ceramic and fiber-cement (white painted) tiles was assessed associated with two types of polypropylene commercial linings (lining A and B) installed below the roof, and a thermo-reflective screen (lining C) installed above the fiber-cement roof. Microclimatic assessment of distorted reduced-scale models was performed at 15-minute intervals by registering the air temperature, black globe temperature, relative humidity and air velocity. Subsequently, black globe humidity index, specific enthalpy, and radiant heat load were calculated. The experimental design was randomized block design with 5 treatments and 15 blocks (replications), totaling 75 experimental units. The reduced-scale models with lining B presented a reduction for all thermal comfort indices. Lining C, installed on the coverage, showed no upgrading of environmental thermal conditions. Thus, lining B presented a better thermal performance regardless the tile type.